Israel : Technical Assistance Report-Reviewing the Fiscal Regime for Mining. (IMF Staff Country Reports; Country Report ;, 2014)
EXECUTIVE SUMMARY This report is provided to support the work of the 'Sheshinski II' committee in reviewing the fiscal regime for mining. Mining is, and will remain, relatively minor both as a source of government revenue and within the wider economy. Nonetheless, it is important that the fiscal regime deliver to the public an appropriate share of the return to the exploitation of resources that they own while also providing investors with a sufficiently attractive and stable environment. To that end, this report reviews principles, experience and tools in mining taxation, bringing them to bear on the analysis of, and suggesting potential improvements to, the current regime. The current use of royalties as the sole and in some cases quite burdensome special fiscal instrument for mining is problematic. One of the primary benefits of royalties-that they ensure some revenue from the start of production-is of limited relevance in Israel, where production is highly mature and exploration minimal. More to the fore is their ineffectiveness in achieving one of the primary goals that warrants a special fiscal regime in the extractive industries: the prospect of designing a charge on rents-returns, that is, in excess of the minimum required by the investor-that can raise revenue without distorting commercial decisions. Their insensitivity to profitability means that royalties not only fail to do this, but, perversely, imply that the government actually takes a smaller share of rents when commodity prices are high; and, conversely, that the company faces a very high effective tax on its profits when those profits are low. Simulations reported here show that these undesirable effects are very marked under the current fiscal regimes. Indeed cutting top marginal royalties-even in the absence of any other reform-would in some cases almost certainly increase both government revenue and after-tax profits. Alternative fiscal regimes-combining a modest mineral-specific royalty with a common profit-based tax-would resolve this structural weakness. The focus of the report is not on the level of the 'government take' from minerals-ultimately a political choice-but on how that take varies with the profitability of the underlying investment. To that end, it reports illustrative simulations (for a hypothetical but not unrealistic project) of alternative fiscal regimes that imply the same government take in a benchmark case but respond very different to project profitability. These alternatives combine a relatively low royalty-which may have some merit in protecting the base against tax avoidance through cost manipulation-with four alternative forms of profit-based tax (retaining, in all but one, the current corporate income tax); and consider too the possibility of converting the royalty into, in effect, prepayment of a profit-based tax. These options differ in important ways-in the required statutory rate of the profit tax, transitional issues, and the time path of government revenues. But they all address the key structural problem, providing structures in which the effective tax rate is lower, not higher, for less profitable outcomes. Fiscal regimes of broadly this kind are (increasingly) commonplace in mining, including in major mineral producing countries. The treatment they provide would be similar to, but could be simpler than, that adopted for oil and gas following 'Sheshinski I.'.